The Relation Between Current Account Deficit and Tourism: The Case of Turkey - Aykaç Alp, Elçin; GENC, Elif GUNEREN (International Journal of Economics and Financial Issues, 2015)
In this study the effects of service’s balance, tourism balance and current account deficit are studied. In the countries with a relatively small share in the current account of the tourism industry, the analysis related to tourism and foreign trade has biased results. For this reason, this study examines how the tourism industry affects the service industry and by this means how it affects the current account balance. The second important issue is that linear time series methods are inadequate because of the nature of the structure of the variables. Keywords: The current account balance; Service industry; Tourism Industry; Threshold Autoregressive Vector Error Correction Models JEL Classifications: C52; F32; L83